The Influence of Work Environment Factors, Employee Motivation and Safety Culture on Patient Safety Performance - Esterlina Mitakda; Prima Dewi Kusumawati; Indasah Indasah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Ensuring patient safety is a critical aspect of healthcare services, influenced by various factors, including the work environment, employee motivation, and safety culture. A well-structured work environment, high motivation levels, and a strong safety culture are expected to enhance healthcare workers' performance in maintaining patient safety. However, the extent of these influences needs further investigation. This study aims to analyze the relationship between work environment, work motivation, and safety culture with patient safety performance in a healthcare setting. A quantitative approach was applied using a cross-sectional study design. Data were collected from 165 healthcare workers through a structured questionnaire. The questionnaire did not undergo validity and reliability testing because it was adopted from previously validated and widely used instruments in prior research. Since the questionnaire has already been tested for accuracy and consistency in measuring the intended variables, further validity and reliability assessments were deemed unnecessary. The Spearman correlation test was used to examine the relationship between variables, while ANOVA was conducted to assess the combined influence of the independent variables on patient safety performance. The findings revealed a significant positive correlation between patient satisfaction and healthcare service quality (p = 0.000). Similarly, work motivation was significantly correlated with patient safety performance (p = 0.0), with respondents consistently rating motivation as good. Safety culture also showed a significant positive correlation with patient safety performance (p = 0.041), with a correlation coefficient of 0.065, indicating a moderate relationship. The study concludes that a supportive work environment, high work motivation, and a strong safety culture contribute significantly to patient safety performance.